Living off the land : agriculture in Wales c. 400 and 1600 ad - Comeau, Rhiannon; Seaman, Andy (Windgather Press, 2019)
This is the first book in a generation on medieval agriculture in Wales, presenting evidence which is of considerable relevance to those studying the development of the early medieval landscapes of England and Ireland. This collection of essays confronts the paradox that, though agriculture lay at the heart of medieval society, understanding of what this meant for Wales remains limited. The papers address key questions that include: how did the agricultural systems of Wales operate between c. 400 and 1600 AD? What light do they cast on the material evidence for life in the contemporary landscape? How similar or different was Wales to other areas of Britain and Ireland? Can we identify change over time? How do we go about researching early Welsh agriculture?These issues are explored through new syntheses and case studies focused on Wales, and contextualising overviews of medieval agricultural systems in Ireland and England written by leading experts. Themes covered include the use of infield-outfield systems, seasonal land use and its impact on territorial and estate structures, and regional variation, all explored using a wide array of complementary multidisciplinary approaches. The introduction, written by the editors Rhiannon Comeau and Andy Seaman, gives context to the historiography, key debates, themes, and issues surrounding this topic. The book also includes an afterword written by Professor Andrew Fleming